2022
DOI: 10.1007/s13178-022-00745-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Minority Stigma and Nonsuicidal Self-Injury Among Sexual Minorities: the Mediating Roles of Sexual Orientation Concealment, Self-Criticism, and Depression

Abstract: Introduction Nonsuicidal self-injury (NSSI), a significant predictor of suicide, is more frequent in sexual minorities (e.g., lesbian, gay, and bisexual) than in heterosexuals. The Minority Stress Model proposed that sexual minority stigma (SMS) may lead to maladaptive behaviors, including NSSI. However, the potential mechanism underlying the relationship between SMS and NSSI remains unclear. Therefore, the current study will examine the relationship between SMS and NSSI, and explore the serial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…In this study, the mean scores of the SMS of the participants were stable, with: 15.3 in wave I, 15.7 in wave II, and 15.5 in wave III, this result is similar to studies conducted in other parts of China (Chen et al, 2022; Tan et al, 2022). The rate of DS among YMSM in all three waves of the survey was stable, fluctuating around 50% (52.4% in wave I, 49.6% in wave II, 50.1% in wave III), consistent with similar studies.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the mean scores of the SMS of the participants were stable, with: 15.3 in wave I, 15.7 in wave II, and 15.5 in wave III, this result is similar to studies conducted in other parts of China (Chen et al, 2022; Tan et al, 2022). The rate of DS among YMSM in all three waves of the survey was stable, fluctuating around 50% (52.4% in wave I, 49.6% in wave II, 50.1% in wave III), consistent with similar studies.…”
Section: Discussionsupporting
confidence: 89%
“…Hatzenbuehler's (2009) psychological mediation framework suggests that this decreased hedonic and eudaimonic well-being reported by LGBTQIAP+ individuals is due, in part, to their experience of minority stress. Indeed, minority stress is associated with reduced hedonic (i.e., depression, suicide ideation) and eudaimonic (i.e., social connectedness) well-being (Baams et al, 2015;Chen et al, 2022;Chodzen et al, 2019). We contend that authenticity may be a yet underrecognized process that also contributes to this reduced well-being subsequent to minority stress experience.…”
Section: Well-being and (In)authenticitymentioning
confidence: 90%
“…That is to say, self‐criticism, as a vulnerable self‐schema, can be seen as an underlying psychological cognitive process that is possibly dynamic and mutable rather than fixed and unchangeable (Blatt, 1974). Chen et al (2022) found a positive association between sexual minority stigma (i.e. perceived stigma and enacted stigma) and self‐criticism in 666 sexual minority individuals.…”
Section: Introductionmentioning
confidence: 99%